THE AFRICAN DIASPORA AND ITS INFLUENCE IN THE IMAGINED COMMUNITY: THE CASE OF CAPOEIRA. (Fiep Bulletin - online, 2014)
The development of a unique identity, from its many categories identities, personal or individual, gender, collective, regional or national is present in dominant ideologies since the French Revolution with the formation of Member Nations, which came a reading innovative training character / identity of a people / nation (Hobsbawm, 2000). This study was designed to ascertain the extent to which the African Diaspora can be as an agent of the transformer imagined community of Capoeira, in order to characterize it as a unifying identity of a group to check the Capoeira community as imagined.
Keywords: Capoeira; Social Representation; Imagined Community; Identity